2016
DOI: 10.1002/adv.21677
|View full text |Cite
|
Sign up to set email alerts
|

Flame‐Retardant Mechanism of Benzoxazine Resin with Triazine Structure

Abstract: Benzoxazion resins have attracted a great deal of interests due to their excellent flame-retardant property. In this paper, a benzoxazion resin with a triazine structure was synthesized successfully and the flame-retardant mechanism of the resin was discussed. Its flammability property and the thermal decomposition were measured and analyzed with a cone calorimeter and thermogravimetry-differential scanning calorimetry-mass spectrometry. The chemical structure as well as the surface morphology of the cured res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…From the LOI results, it can be found that the MFF and MFF‐TFMB fibers have good flame‐retardant properties. Because the high nitrogen content of the triazine ring has an inhibitory effect on fiber burning 6 . At high temperatures, the nitrogen‐containing groups of the triazine ring decompose into non‐combustible gases, which can dilute the oxygen in the air and reduce the concentration of combustibles generated by the thermal decomposition of polymers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the LOI results, it can be found that the MFF and MFF‐TFMB fibers have good flame‐retardant properties. Because the high nitrogen content of the triazine ring has an inhibitory effect on fiber burning 6 . At high temperatures, the nitrogen‐containing groups of the triazine ring decompose into non‐combustible gases, which can dilute the oxygen in the air and reduce the concentration of combustibles generated by the thermal decomposition of polymers.…”
Section: Resultsmentioning
confidence: 99%
“…Because the high nitrogen content of the triazine ring has an inhibitory effect on fiber burning. 6 At high temperatures, the nitrogen-containing groups of the triazine ring decompose into non-combustible gases, which can dilute the oxygen in the air and reduce the concentration of combustibles generated by the thermal decomposition of polymers. Nitrogen oxides generated by thermal decomposition can capture free radicals and inhibit the chain reaction of polymer combustion, thereby achieving the purpose of flame retardant.…”
Section: Flame-retardant Properties Of Fibersmentioning
confidence: 99%
See 2 more Smart Citations
“…These detected inert gases can dilute the concentration of combustible gases, thereby achieving a flame-retardant effect. 37,38,43 Moreover, the microscale combustion calorimeter (MCC) was used to measure the heat release rate of NNS-VCOF aerogel against temperature. From the curves, quantitative information related to the combustion properties of aerogels can be obtained including the peak heat release rate (PHRR) and corresponding temperature (TPHRR), total heat release (THR), heat release capacity (HRC), as listed in Figure 4i inset table.…”
Section: ■ Introductionmentioning
confidence: 99%